Treatment outcomes of archwise distraction osteogenesis in mandibular dentoalveolar retrognathia cases - ACAR, YASEMİN BAHAR (CHURCHILL LIVINGSTONE, 2017)
The aim of this study was to describe the treatment of class II malocclusion by sagittal advancement of the alveolar bone in the symphyseal area using an intraoral archwise distractor device and to determine the effects of this method on the dentoalveolar complex. Fifteen patients (10 female, five male) aged 16-20 years with a class II division 2 malocclusion, characterized by mandibular dentoalveolar retrusion and a prominent chin, underwent archwise alveolar distraction in the anterior mandible. Lateral cephalometric radiographs were obtained before distraction (TO), after 6 weeks of consolidation (T1), and after debonding (T2). Linear and angular skeletal, dental, and soft tissue measurements were performed. Forty-seven parameters were measured for each of the 15 subjects on pre- and postoperative lateral cephalometric radiographs (TO, T1, and T2). The distraction protocol was successful in all patients. Skeletally, the mandible showed a clockwise rotation. B-point moved forward significantly (P < 0.05). Overjet decreased significantly (P < 0.001). The total profile angle was unaffected, and the improvement in the submental fold was highly significant (P < 0.001). The intraoral archwise distraction force that is applied through brackets and archwires is sufficiently effective for alveolar advancement. This procedure is simple and effective in the treatment of specific adult patients with a class II division 2 malocclusion, characterized by a prominent chin and severe mandibular dentoalveolar retrusion.
Keywords: alveolar distraction osteogenesis; mandibular dentoalveolar retrusion; archwise distraction; INFERIOR ALVEOLAR NERVE; SAGITTAL SPLIT OSTEOTOMY; SEGMENTAL DISTRACTION; HERBST APPLIANCE; ADVANCEMENT; STABILITY; RELAPSE; DEVICE